Private versus Public Hospitals: Patient Satisfaction of Nursing Care Quality in Orthopaedic Wards - Ali, Zahraa Hussein; AL-Fayyadh, Sadeq; Isam, Safad Riyadh; Hussein, Shaymaa Mohammed; Al-Ganmi, Ali Hussein Alek; AL-Hadrawi, Hayder (The Nigerian postgraduate medical journal, 2025)
Background: Patient's satisfaction with nursing care is thought to be a key component in determining how patients perceive service quality. Quantifying patient satisfaction in both private and public healthcare settings can offer essential evidence on performance; consequently, reflected on quality management. Aims: This study aims to explore patients' satisfaction with the quality of nursing care. Subjects and Methods: A descriptive-cross-sectional study was conducted, involving 251 patients selected through a random selection method. Data were collected using the patient satisfaction with Nursing Care Quality Questionnaire, comprising a total of 20 items. The collected data were then analysed and interpreted using descriptive and inferential statistics. Data were analysed using SPSS V25. Results: The findings of the current study show that more than half (52.6%) of subjects were somewhat satisfied with the provided nursing education. Similarly, more than half (55%) of subjects were somewhat satisfied with the provided nursing care. Correspondingly, (60.2%) of subjects were somewhat satisfied with the overall provided nursing services, including both the educational and the actual direct nursing care. Conclusions: Overall, patients expressed general satisfaction with the inpatient nursing care they received, and their perceived needs and care expectations from nurses significantly influenced their satisfaction levels.